ACUTE INTAKE OF YERBA MATE INCREASES ENERGY EXPENDITURE OF HEALTH YOUNG MEN: A PILOT STUDY - Oliveira, Erick Prado de; Torezan, Gabriel Augusto [UNESP]; Goncalves, Livia de Souza [UNESP]; Corrente, Jose Eduardo [UNESP]; Portero McLellan, Katia Cristina [UNESP]; Burini, Roberto Carlos [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2016)
Background: Yerba mate has been studied as anti-obesity factor, mainly because of its thermogenic effect, however, few studies were performed in humans. Objective: We aimed to evaluate the acute effect intake of yerba mate on energy expenditure in healthy adults. Methods: It was evaluated 9 health men and study design was cross-over placebo controlled. In the placebo group the individuals ingested 500 ml of water and in intervention group it was consumed 5 g of soluble yerba mate diluted in 500 ml of water. After one hour, energy expenditure was measured during 30 minutes by indirect calorimetry. Interventions were separated by a washout period of 7 days. Results: After yerba mate intake it was showed higher energy expenditure (similar to 125 kcal) (p<0.05) comparing with water group. Evaluating individually, the majority of individuals increased energy expenditure after yerba mate intake, however two individuals did not show any change. Conclusion: Acute intake of yerba mate increased energy expenditure of health young men.
Keywords: Ilex paraguariensis; Energy Expenditure; Diet